Rancang Bangun Alat Arduino Uno Menggunakan Sensor Ultrasonik Sebagai Radar dalam Materi Gelombang - Lisa Listyo Wati; Intan Yuanita Permata Putri; Irene Widya Siswanti; Dinda Twizatur Rizka; Rohmi Khoirunnisa; Alex Harijanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
Wave is one of the materials taught at the high school level (High School) and equivalent. Wave lessons can be developed through technology, unfortunately very difficult to implement especially in small towns and rural areas. This study aims to design an Arduino tool using an ultrasonic sensor as a radar in wave material. The research uses four stages, namely: hardware design, software design, teaching aids making and teaching aids testing. The results of the Arduino design based on ultrasonic sensors in the processing software display a detectable distance, which is a maximum of 40 cm equipped with an angle.